Automated System to Prioritize Highway Improvement Locations and to Analyze Project Alternatives. Issue 1 (2017) - Gan, Albert; Alluri, Priyanka; Raihan, Md Asif; Liu, Kaiyu; Saha, Dibakar; Jung, Rax
The Florida Department of Transportation (DOT) District One first deployed a web-based system in 2009, called the Congestion Management Process (CMP), to screen and prioritize highway locations on its Strategic Intermodal System (SIS) for low-cost, near-term improvements. The system prioritizes highway locations on the SIS within the district on the basis of a simple scoring method with seven performance measures (i.e., crash ratio, fatal crash, volume-to-capacity ratio, average annual daily traffic, truck volume, truck percent, and delay). Once the Florida DOT adopted the Highway Safety Manual (HSM), there was a desire to apply safety performance measures to the CMP that were consistent with the manual's methodology. There also was a desire to explore and implement a more advanced project prioritization method for better location screening and prioritization and to add mapping capabilities to improve data visualization. This paper describes the district's efforts to incorporate these improvements into the CMP system. The CMP system can calculate performance measures automatically, including two safety-related measures on the basis of the HSM methodology, and prioritize highway locations with the Analytic Network Process, an advanced multicriteria decision-making technique. The system can create thematic maps of performance measures and other input variables on Google Maps for data visualization. It also can evaluate potential projects and record project-level information. Although developed for the Florida DOT District One, the system can serve as a prototype and be customized to prioritize highway locations in other states.